Influence of two pt(iv) complexes on viability, apoptosis and cell cycle of B16 mouse melanoma tumors - Kaznica, A.; Drewa, T.; Lakomska, I.; Ryta-Stamirowska, P.; Debski, R.; Styczynski, J.; Drewa, G.; Szłyk, E. (Experimental Oncology, 2009)
Several platinum(IV) complexes are showing considerable promise in initial trials, producing reactive intermediates that then interact with DNA. Aim: To perform in vitro study of two new platinum(IV) complexes cytotoxic effect on B16 mouse melanoma cells. Methods: PtCl₄ (dbtp)₂ and PtCl₂ (6mp)₂ complexes were prepared. PtCl₄ (dbtp)₂ was created as modification of PtCl₄ (dmtp) test previously.Apoptosis and necrosis were examined using flow cytometry, upon Annexin V/PI staining. Results: LC₁₀,LC₅₀ andLC₉₀ parameters established for PtCl₄ (dbtp)₂ were as following: 2.6, 17.0, 58.0 μmol/L. However LC₁₀ andLC₅₀ established for PtCl₂ (6mp)₂ were 1.2 and 14.0μmol/l respectively. The both complexes induced apoptosis. PtCl₂ (6mp)₂ induced cell cycle arrest in G0/G1, while PtCl₄ (dbtp)₂ — in S-phase. Conclusions: PtCl₄ (dbtp)₂ appeared to be more cytotoxic against B16 cells than PtCl₂ (6mp)₂ . Apoptosis was the main mechanism of cell loss in cultures incubated with both tested complexes.